Respuesta :

Answer:

6[tex]\frac{1}{3}[/tex]

Step-by-step explanation:

4x-12 = x+7

4x-12+12 = x+7+12

4x = x+19

4x-x = x+19-x

3x=19

x = 6[tex]\frac{1}{3}[/tex]

And if we substitute the value of x into the equation 4x-12 = x+7,

we will get 13[tex]\frac{1}{3}[/tex] = 13[tex]\frac{1}{3}[/tex] in the end.

Hope this helps :)

Answer:

19/3 = [tex]6\frac{1}{3}[/tex]

Step-by-step explanation:

[tex]4x -12= x+7\\Collect-Like-Terms\\4x-x =7+12\\3x=19\\Divide -Both-Sides-Of-The-Equation-By ; 3\\\frac{3x}{3} =\frac{19}{3} \\\\x = \frac{19}{3}\\ \\x = 6.3\\[/tex]